Joining of alumina ceramics with Ti and Zr interlayers by spark plasma sintering. (March 2023) - Stosz, Maria; Narayanasamy, Sathya; Bell, Jon; Graule, Thomas; Kata, Dariusz; Blugan, Gurdial
Graphical abstract: Highlights: In this study, alumina ceramics were joined by Spark Plasma Sintering (SPS) technology with titanium and zirconium metals applied as interlayers. In the current state of art, titanium successfully joined alumina by SPS for the first time, while bonding with zirconium was not previously mentioned in the literature. Titanium joined with alumina at 700, 800, and 900 °C (force 3 kN), however, the bond from 800 °C stands out with the highest integrity and stability among others. The formation of oxides and metallic compounds are the expected result of the SPS treatment. Zirconium-alumina bonding was achieved at 800, and 900 °C (force 4.2 kN). The higher temperature resulted in the better quality of bonding, but worse than the titanium systems. The ZrO2 formation could decrease the stability in the joined system. Abstract: In this study, alumina ceramics were joined by spark plasma sintering technology using zirconium and titanium metals as interlayers. Bonding with Zr was achieved at 800 and 900 °C with an applied force of 4.2 kN, and then at 900 °C with a force of 3 kN. It was found that Ti bonded to alumina at 700, 800, and 900 °C with an applied force of 3 kN. The influence of temperature and pressure on the bonding properties was measured for both interlayers. Scanning Electron Microscope was used to examine the quality of the bonded ceramics and Energy Dispersive X-ray spectroscopy was used to gain insights into the bonding mechanism. The best joints were obtained at 900 °C for Zr and 800 °C for Ti. Oxygen diffusion via the formation of oxygen defects/vacancies and the formation of reaction products such as ZrO2 (and some Ti-Al or TiO2 reaction products) could underpin the possible bonding mechanisms.